2023
DOI: 10.1021/acs.jpcc.3c01917
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Induced Phase Transformations in CuO Thin Films by Ag Ion Implantation and Their Gas-Sensing Applications

Abstract: The present study is aimed to modify the structural, optical, and morphological properties of CuO thin films with Ag ion implantation toward their potential applications. Fabrication of thin films of CuO was carried out using a thermal evaporation technique on silicon (Si) substrate; post implantation was done with 30 keV Ag ions with varying fluences from 1 × 1014 to 1 × 1016 ions/cm2. The pristine and implanted samples were characterized through X-ray diffraction (XRD), Raman spectroscopy, atomic force micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The ions implanted in the material lose their energy via excitation of target’s electrons or collisions with nuclei. For energies in the range of keV, the nuclear stopping is predominant 26 . Collisions with target atoms cause them to move from their positions in the crystal lattice, the crystal structure is damaged and can be amorphized with enough implanted ions 21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ions implanted in the material lose their energy via excitation of target’s electrons or collisions with nuclei. For energies in the range of keV, the nuclear stopping is predominant 26 . Collisions with target atoms cause them to move from their positions in the crystal lattice, the crystal structure is damaged and can be amorphized with enough implanted ions 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Another utilization of ion implantation was performed by Shi et al 25 , who used argon ions to introduce defects into CuO to study the magnetic properties of the material. High energy 2 MeV Ar ions with doses of 1 × 10 15 and 5 × 10 15 cm −2 produced an increased amount of the Cu vacancies and cause a phase change of CuO into Cu 2 O. Yadav et al 26 implanted CuO thin films of 220 nm thickness with Ag ions of 30 keV energy and doses between 1 × 10 14 and 1 × 10 16 cm −2 . They found that with higher dose the crystallinity of material decreased, and they also noticed a phase change—into Cu 2 O and even Cu for the highest implantation dose.…”
Section: Introductionmentioning
confidence: 99%